The Analysis Of Violence On The Rod Front Suspension 785 Caterpillar Before And After Welding GMAW (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2022)
Hardness (hardness) is one of the mechanical properties (Mechanical Properties) of a material. The hardness of a material must be known, particularly for materials that are in use will have an emphasis and friction. To determine the value of the hardness of the material with the hardness testing using the tool hardness tester. One of the hardness testing that is done on the surface of the rod front suspension unit dump truck 785 CATERPILLAR that has been done the welding process on the surface of the rod front suspension. The purpose of this study is to determine the hardness after the process of welding rod front suspension before and after welding GMAW.This research was conducted in September through November 2020. The research took place in PT. The mainstay of Fluid Systems that are located in the area of Jl. Soekarno Hatta Km.29, Kec. Samboja, Kab. Kutai Kartanegara, East Kalimantan. The object of research is focused on the surface of the rod front suspension and using 2 samples of the material AISI 1045 to determine the effect of the comparison of cooling where the material is the basic material of the rod front suspension.After analysis it was concluded that the violence that occurred after the welding process is not so experienced many significant changes that range 47,2 – 48 HRC which the value of the numberless still msauk in the standards set by the CATERPILLAR